TEACHING PHYSICS IN CONNECTION WITH ECOLOGICAL PHENOMENA AND PROCESSES (TAMADDUN NURI JURNALI, 2024)
The article explains the issues of environmental content, taking into account the goals and objectives, forms, didactic principles of teaching physics. By choosing, formulating and solving various issues of physical and environmental content, he introduces students to the physical foundations and features of the country's ecology. It also talks about how to achieve success by conducting physical events, and how to teach physics to surrounding environmental phenomena and processes.